POVERTY ALLEVIATION AND THE CONTROL OF PUBLIC REVENUE IN NIGERIA: LEGAL AND EQUITABLE ISSUES (The Pretoria Student Law Review, 2021)
Apart from the dreaded Acquired Immune Deficiency Syndrome (AIDS) now ravaging the world, and particularly the African continent, no other scourge has had such a devastating impact on both the ancient and modern world as the scourge of poverty. According to the World Health Organisation, poverty wields its destructive influence at all stages of human life, from the moment of conception to the grave. It conspires with the most deadly and painful diseases to bring a wretched existence to all who suffer from it. The desire to alleviate, or if possible, eliminate poverty, has engaged the attention of successive governments in Nigeria: Civilian, quasi-civilian and military administrations. At present the world is still in search of a solution to global poverty, which is why the United Nations currently puts poverty reduction at the top its agenda. The continual search for ways to achieve poverty alleviation in Nigeria, particularly as it relates to the legal and equitable issues involved, is the topic of this paper. However, first it is important to define terms so as to make for clarity of thought, better understanding and for consensus ad idem.
Keywords: Acquired Immune Deficiency Syndrome (AIDS); World Health Organisation; poverty; poverty reduction; Nigeria; successive governments; military administrations; quasi-civilian; civilian